Experimental study of desulfurization of chemical-loping combustion of coal with calcium-based oxygen carrier - Zhang,S; Xiao,R; Yang,YC; Song,QL (Kung Cheng Je Wu Li Hsueh Pao Journal of Engineering Thermophysics, 2012)
In the process of chemical-looping combustion of coal with calcium-based oxygen carrier, large amount of SO 2 was released due to the side reactions occurred between CaSO4 oxygen carrier and coal gasification products. In this work, desulfurization experiments were conducted using MAC iron ore, CaO and limestone as desulfurizers in a laboratory scale pressurized fixed-bed reactor. The influencing factors of temperature, pressure and Ca/S ratio on the removal of SO 2 gas were analyzed. The results showed that the outlet concentration of SO 2 increased with the increase of temperature in the presence of only CaSO 4 oxygen carrier. Adding MAC iron ore into the reactor could reduce the concentration of SO 2 released from the reactor due to the catalytic effect of Fe 2O 3 on suppressing the decomposition of CaSO 4. The desulfurization efficiency of both CaO and limestone showed an increased trend with the increase of temperature, pressure and Ca/S ratio, and CaO showed a better performance than limestone under the same experimental conditions.